First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female - Rippel, Mellis Layra Soares; Novaes, Marcos Carneiro; Krolow, Tiago Kütter (Zootaxa, 2019)
The genera Macrogynoplax Enderlein, 1909 and Kempnyia Klapálek, 1914 are reported for the first time from Tocantins State, a new locality record for Brazil. The nymphs of M. matogrossensis Bispo & Neves (2005) and K. goiana Bispo & Froehlich (2004) are described. Additionally, we also describe the female of K. goiana.